Liver fibrosis and markers of endothelial function at metabolic syndrome and early disorders of carbohydrate metabolism - L. V. Chesnokova; I. M. Petrov; Ye. A. Sidorova; I. A. Troshina; Yu. A. Petrova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Complex estimation of endothelial function at non-alcoholic fatty liver disease (NAFLD) in association with early disorders of carbohydrate metabolism, in relation to liver fibrosis severity.Material and methods. Overall 67 patients with metabolic syndrome (MS) in combination to early carbohydrate metabolism disorders (71,6% women), mean age was 47,5 (42–49 years), body mass index — 34,6 kg/m2 (32,4–38,4 kg/m2) were investigated. In 72% of patients presence of NAFLD at steatosis stage and in 18% —at non-alcoholic steatohepatitis stage was found.Results. In patients with MS in association to early disorders of carbohydrate metabolism liver fibrosis at F1 METAVIR stage was revealed in 25%, at F2 — in 16%, at F3 — in 13% and at F4 — in 1,5% of all cases. Along with increase of fibrosis stage progressive elevation of TNF-α (p=0,0265), IL-6 (p=0,0012) and endothelin-1 (p=0,0137) contents on background of decrease of adiponectin concentration (p=0,0026) and gain of humeral artery diameter after compression (p=0,005) was marked.Conclusions. Presence and severity of liver fibrosis at MS in combination to early disorders of carbohydrate metabolism are related to increase of proinflammatory cytokines, endothelin-1 concentration on a background of reduction of adiponectin contents and decrease of endothelium vasodilation capacity.